2006
DOI: 10.1359/jbmr.060403
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in OSTM1 (Grey Lethal) Define a Particularly Severe Form of Autosomal Recessive Osteopetrosis With Neural Involvement

Abstract: We report three novel osteopetrosis patients with OSTM1 mutations and review two that have been previously described. Our analysis suggests that OSTM1 defines a new subset of patients with severe central nervous system involvement. This defect is also present in the gl mouse, which could represent a good model to study the role of the gene in the pathogenesis of this disease.Introduction: Autosomal recessive osteopetrosis (ARO) is a severe hereditary bone disease whose cellular basis is in the osteoclast, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
73
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 28 publications
7
73
1
Order By: Relevance
“…(1,(5)(6)(7)(8)(9)(10) The SNX10 gene was amplified using primers and conditions kindly provided by Aker and colleagues (Hebrew University Medical Center, Jerusalem). The mutation nomenclature conforms to www.hgvs.org/mutnomen.…”
Section: Molecular Studiesmentioning
confidence: 99%
“…(1,(5)(6)(7)(8)(9)(10) The SNX10 gene was amplified using primers and conditions kindly provided by Aker and colleagues (Hebrew University Medical Center, Jerusalem). The mutation nomenclature conforms to www.hgvs.org/mutnomen.…”
Section: Molecular Studiesmentioning
confidence: 99%
“…However, the primary cell sources of the secreted form of the truncated OSTM1 remain unknown. Interestingly, the gray-lethal mutation leads not only to osteopetrosis but also to coat color defects and neurological damage (5). Furthermore, a recent study demonstrated that a loss of function of the Ostm1 gene results in the deregulation of multiple hematopoietic lineages, including Tand B-cells, in addition to OC lineage cells (34).…”
Section: Discussionmentioning
confidence: 99%
“…The subset of patients (5% in our cohort) displaying mutations in OSTM1 gene, encoding for a protein involved in late endosomal-lysosomal trafficking, functionally and physically linked to ClCN7 (Lange et al 2006;Meadows et al 2007), is characterized by even more serious neurological defects (neurodegeneration, optic atrophy, microcephaly, cortical atrophy; in one case, bilateral atrial subependymal heterotopias) (Chalhoub et al 2003;Quarello et al 2004;Ramirez et al 2004;Pangrazio et al 2006;Castellano Chiodo et al 2007;Maranda et al 2008). These findings strongly discourage HSCT, because, even if the transplant engrafted, the patient would die due to the severe CNS defects; indeed, in our series no OSTM1-dependent patients have been transplanted.…”
Section: Treating Human Aro: the Osteoclast-rich Formsmentioning
confidence: 96%